Purification and Characterization of a Thermostable Xylanase Cloned from Bacillus Coagulans ST-6 - Yow, Geok Yong (1997)
The recombinant plasmid pBNX contains a xylanase gene cloned from a thermophilic Bacillus coagulans ST -6. It was found to produce a high level of intracellular xylanase activity in Escherichia coli HB 10 1. This xylanase enzyme was purified to homogeneity via a single step chromatography using a Sephadex G-50 column. SDS-PAGE analysis showed a single protein band having a molecular mass of 20 kDa. Zymogram analysis using agarose gel electrophoresis showed a single activity band for both crude and purified enzyme. Isoelectric point of the purified xylanase was pH 9.3. The optimum temperature and pH for xylanase activity was 55°C and pH 7.2 respectively. The enzyme was found to be stable and retained its activity after 30 min incubation at 60°C. The enzyme showed a broad range of pH stability, in that it retained its activity after a 1 hr incubation at pH 5 to pH 10.The apparent Km and Vmax of the enzyme was 2.18 mg/ml and 147.6 ).lmol xylose/min/mg protein respectively using oat spelt xylan as the suostrate. The purified enzyme was found to have very low CMCase activity after prolonged incubation of 5 hr to 24 hr (less than 5% that of xylanase activity after 24 hr incubation). No activity towards Avicel and filter paper was observed. No xylose, xylobiose or arabinose was found in the end product analysis using TLC indicating that the xylanase was a nondebranching endoxylanase. The effect of various metal ions on the measurement of reducing sugar by Somogyi-Nelson and DNS methods was examined. At 1 mM, Ca2+, Mn2+ and Pb2+ increased colour intensity of the standard glucose measured by DNS method while Mg2+, Zn2+, Hg2+ and EDTA decreased the colour formation. For the SomogyiNelson assay, only Mn2+ and Hg2+ decreased colour intensity of standard glucose measured while other compounds showed no effect. A subsequent study on the effect of metal ions on xylanase activity, taking into consideration of these results, showed that only Hg2+ was inhibitory while other metal ions (Li+, K+, Na+, Ca2+, Mg2+, Co2+, Mn2+, Cu2+, Zn2+, Pb2+ and Fe2), EDTA, urea and SDS had no effect.